The Leadership Strategy of Madrasah Head in Improving Prospective Students' Interest - Yanto, Wakhid Nur; Joko Raharjo, Tri; Prihatin, Titi (Educational Management, 2020)
Students are both subject and object in educational institutions. The number of students has a significant impact on the existence of educational institutions. Competitive competition encourages educational institutions to innovate in the promotion of educational services. The purpose of this study was to describe and analyze; 1) Strategic plan; 2) Strategic steps of Madrasah Head in increasing the interest of prospective students at MIN 1 Kendal Kendal Regency. The research method was qualitative and the design was case study, the process of collecting data was observation, interview and document study. The results showed: 1) There was increasing of short-term and long-term strategic plan using SWOT analysis; 2) Creating madrasa differentiation as a superior program; 3) Improving the culture of discipline; 4) Optimizing the extra-curricular activities to improve student achievement; 5) Determining tuition fee; 6) Improving the quality of the teachers; 7) Improving the quality of teaching and learning activities; 8) Promotion strategies were divided into promotion strategies through the new student admission committee (PPDB) and through activities organized by madrasa. The suggestion related to the result of this study was madrasa should make the mapping of the region as a promotional target and move more quickly in meeting the madrasah facilities and infrastructure.